Making data science a sport - Goldbloom, Anthony; Safari eBooks; O'Reilly strata making data work conference (2011 : Santa Clara, Calif.) ([United States?] : O'Reilly Media, 2011)
"Data modeling competitions allow companies and researchers to post a problem and have it scrutinised by the world's best data scientists. By exposing a problem to a wide audience, competitions are a great way to get the most out of a dataset. In just a few months, Kaggle's competitions have helped to progress the state of the art in chess ratings and HIV research." --Resorce description page.
Title from title screen.
Recorded at O'Reilly strata making data work conference: Feb. 1-3, 2011, Santa Clara, Calif.
Electronic reproduction.
Keywords: Relational databases; Database design; Electronic books